Effect of strain rate on microstructure and mechanical properties of hot stamping quenching-partitioning steel - WU Cong; JING Cainian; LIN Tao; YE Daomin; LEI Qiteng (Cailiao gongcheng, 2022)
A split Hopkinson pressure bar was used to perform dynamic compression experiments on HS-Q&P steel at the strain rates of 0-12000 s-1. The deformation behavior of the specimen during dynamic compression was studied by SEM, EBSD, XRD characterization methods. The results show that the deformation behavior of the experimental steel at different rates is similar and is divided into three stages. First, there is a slight increase in stress at the platform, but the increase is more reflected in the strain. The adiabatic heating effect that occurs during the compression process will bring a softening effect. The strength and plastic deformation ability of the experimental steel can be improved by the retained austenite. The volume fraction of retained austenite in steel reduced by the transformation induced plasticity (TRIP) effect is the same as the volume fraction of martensite increased and proves the TRIP effect is the main strengthening mechanism in the steel. At the same time, it is observed by SEM that the retained austenite is transformed into acicular martensite by the TRIP effect. As the strain rate increases, the lattice distortion becomes more and more serious, and some deformation twins can be observed in the EBSD maps. At different strain rates, 〈001〉oriented grains are more likely to produce deformation twins.